THE IMPACT OF ADDRESS COMPOUND CONCENTRATED FEEDSTUFF ON THE DAIRY PRODUCTIVITY OF COWS AND THE QUALITY OF MILK - Kalmagambetov Murat Baytugelovich,; Ombaev Abdirahman Moldanazaruly,; Ashanin Alexander Ilyich ,; Adaybaev Zhanmukhamed Zharasovich,; Tlepov Anarbek Amreevich, (Academic Journal of Physical and Chemical Sciences, 2019)
As a result of the undertaken research, the chemical composition of feed in the basic farm of the Karimov SP was studied, the detailed rations were developed and the deficiency of biologically active substances was determined in them. The most promising way to eliminate the deficit of minerals and vitamins in feeding animals is to enrich the rations with various feed additives. Of particular topicality is the use of biologically active substances in biogeochemical provinces, which are deficient in a number of macro- and microelements in soils and feeds. Taking into account the needs and content of nutrients, macro- and microelements, as well as vitamins in the diet, their deficiency was determined, which amounted to 54.0% in sugar; 32.6% in phosphorus; 22.6% in copper; 81.1% in cobalt ; 53.1 in zinc; 73.6% in iodine; 38.5% in manganese and 81.4% in vitamin D (IU). Based on the deficit of macro-and micronutrients, as well as vitamins, a recipe for a compound concentrated feedstuff for cows with a productivity of 20-24 kg of milk per day was developed. Along with this, the chemical composition of the compound concentrated feedstuff was determined. The results of experimental studies showed that the eatability of the feed mixture in the control group was 89.46%, and in the experimental group - 93.66%, which is higher by 4.2%, and the dairy productivity of the cows in the experimental group increased by 6.98%, and in terms of 4% milk, this indicator increased by 9.98%, the cost of milk decreased by 4.9%.